AUDIT SISTEM INFORMASI APLIKASI PAJAK PBB P2 BADAN PENDAPATAN DAERAH KABUPATEN WAY KANAN MENGGUNAKAN FRAMEWORK COBIT 2019 - Adison; Sutedi, Sutedi (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2025)
The PBB-P2 tax application in the Revenue Agency of Way Kanan Regency has a critical limitation: it cannot record actual coordinate data, causing tax assessments to rely on predetermined strategic-location values rather than precise geographic information. This study aims to evaluate the information system governance of the PBB-P2 tax application using the COBIT 2019 framework. The research employed a quantitative method with questionnaires distributed to 15 respondents consisting of staff and management of the Revenue Agency. Sampling used purposive sampling, and data validity and reliability were tested using Pearson correlation and Cronbach’s alpha. The assessment covered five COBIT 2019 processes: APO04, APO07, APO13, DSS02, and DSS03. Results show that all five processes are at capability level 3 (Predictable Process) with an average current score of 3.47, while the expected level is 4.49, yielding a gap of approximately 1.02. This gap indicates that the system requires significant improvements in innovation management, human resource competence, information security, and service request management. Recommendations include structured training programs, security system upgrades, and formalized incident management procedures